2021
DOI: 10.1007/s10924-021-02238-8
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stabilization of Recycled PET Through Chain Extension and Blending with PBT

Abstract: This study investigates the effect of using a multifunctional epoxide chain extender (Joncryl® ADR 4468) on the thermal stabilization and rheological properties of recycled polyethylene terephthalate (R-PET) and its blends with polybutylene terephthalate (PBT). The thermal stability of the melt blended samples was analyzed through small amplitude oscillatory shear (SAOS) rheological experiments. The structure of the samples was evaluated using a Fourier transform infrared (FTIR) spectrometer. While the dynamic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…A comparison of the blends containing Joncryl ( Figure 3 ), indicates a significant increase in viscosity—almost double—and a slight decrease in the degradation rate during processing ( Figure 5 ) in PET and blends containing 75% PET, thus proving the efficiency of this additive towards PET. Guclu [ 40 ] investigated the effect of using a multifunctional epoxide chain extender (Joncryl ® ADR 4468) on the thermal stabilization and rheological properties of recycled polyethylene terephthalate and its blends with polybutylene terephthalate, and the reactivity of Joncryl was more noticeable in blends with higher recycled polyethylene terephthalate contents due to the higher available internal reactive sites of much shorter recycled polyethylene terephthalate molecules.…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of the blends containing Joncryl ( Figure 3 ), indicates a significant increase in viscosity—almost double—and a slight decrease in the degradation rate during processing ( Figure 5 ) in PET and blends containing 75% PET, thus proving the efficiency of this additive towards PET. Guclu [ 40 ] investigated the effect of using a multifunctional epoxide chain extender (Joncryl ® ADR 4468) on the thermal stabilization and rheological properties of recycled polyethylene terephthalate and its blends with polybutylene terephthalate, and the reactivity of Joncryl was more noticeable in blends with higher recycled polyethylene terephthalate contents due to the higher available internal reactive sites of much shorter recycled polyethylene terephthalate molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Torque max − Torque time Torque max − Torque min (2) The reaction rate constant can be calculated from the double logarithmic plot of ln [ − ln (Θ)] over ln(t). They found out that the reaction of Joncryl with PLA is generally faster than that with PBSA, due to the lower molecular weight of PLA used in that study.…”
Section: θ =mentioning
confidence: 99%
“…Due to their excellent properties, polyesters such as poly (ethylene terephthalate) (PET) and PBT are classified as engineering DOI: 10.1002/mame.202200683 plastics. [1][2][3] In particular, their enhanced thermal stability and mechanical resistance qualify them for use as construction materials in areas such as the automotive and electrical industries. [1,4,5] For lightweight structures, polyesters are used as foams to save weight while maintaining reliable mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…42,[82][83][84][85][86][87] This is due to its high reactivity with carboxyl acid and hydroxyl end groups that exist specifically in polyesters such as PLA and polyethylene terephthalate (PET) and polyamides. 87 Due to such high reactivity, the rheological properties of polyesters and polyamides could dramatically be improved 78,[87][88][89] and hence their processability could considerably be enhanced. 87,90 It has also been demonstrated that the use of small amount of Joncryl could significantly promote the crystallization of polyesters.…”
Section: Introductionmentioning
confidence: 99%